Post-Chineseness cultural politics and international relations - Shi, Zhiyu, 1958- (SUNY series, James N. Rosenau series in global politics., 2022)
Analyzes international and cultural relationships informed by "China," a category that is becoming ever more indispensable and yet unstable in everyday narratives.